Influence of catastrophe risk on insurance and reinsurance markets - Hana Bártová (European Financial and Accounting Journal, 2017)
Insurance and reinsurance markets are exposed to influence of unsystematic catastrophe risk, which is caused by adverse development in natural disasters. Deepening of influence is highlighted in relation to irregular and extreme impacts of catastrophes. Insurers face to coverage of random loss events with contribution of reinsurers through a transfer of specified part of non-life risk. Influence of catastrophe risk is assessed through analysis of annual and quarterly development in catastrophe losses, impacts of floods, amount of premium written and reinsurance premium with respect to relations among selected variables. Analysis is focused on specific conditions of the Czech insurance market in context of reinsurance market. The findings concern to negative development in increasing catastrophe and flood losses, which seems to be not in line with changes in premium written, respectively reinsurance premium, which remain at stable level during analysed period. Respecting unfavourable aspect of insufficient data, results emphasize inadequate level of reinsurance of significant catastrophe risk, respectively floods, within the Czech insurance market.
Keywords: C58; G22; 650; Catastrophe; Flood; Insurance; Reinsurance